PERLINDUNGAN HUKUM TERHADAP PROFESI DOKTER DALAM MELAKUKAN TINDAKAN MEDIS - T, Emilzon (UNES Law Review, 2022)
Article 27 of Law Number 36 of 2009 concerning Health which states that health workers are entitled to compensation and legal protection in carrying out their duties in accordance with their profession. The approach used is a normative juridical approach which is supported by an empirical juridical approach. Forms of legal protection for the medical profession in carrying out medical actions based on the health law at the Central General Hospital Dr M.Djamil Padang are: 1) Preventive legal protection 2) Progressive legal protection, namely if a doctor makes a mistake in the hospital, then assistance is given law. The legal aid in question is if mediation can be carried out in this case, then mediation will be carried out, if the problem is brought to the court, legal assistance will be provided such as the procurement of a legal team from the dr. M. Djamil Padang, or by bringing in a lawyer from outside or the Ministry of Health. Every medical practice is required to have a medical record, which is a file containing notes and documents regarding the patient's identity, examination, treatment, actions and other services that have been provided to patients. The obstacles found in the legal protection of the doctor's profession in carrying out medical actions at the Dr. M.Djamil Padang General Hospital are: 1) Doctors do not have a media where doctors complain about the rights and obligations of doctors that have been regulated in the health law; 2) Lack of knowledge of some doctors regarding their rights and obligations as doctors, that their rights and obligations have been regulated in the Health Act; 3) Standard Operating Procedures are not up-to-date or have medical personnel but do not have sufficient time to disseminate information on SOPs; 4) the quality standard of medical personnel needs to be improved.